The relationship between inspiratory muscle strength, venous refilling time, disease severity, and functional capacity in patients with chronic venous insufficiency - Aydin, Gamze; Yeldan, Ipek; Akgul, Ahmet (Sage Publications Inc, 2023)
Background Our aim is to evaluate the relationship between inspiratory muscle strength and venous refilling time, disease severity, and functional capacity in patients with chronic venous insufficiency (CVI). Methods Sixty-one patients (49 female, aged 20-65 ) were enrolled in the study. The demographic characteristics of the patients were questioned. All patients were assessed with maximum inspiratory and expiratory pressure (MIP/MEP) for inspiratory and expiratory muscle strength, photoplethysmography for venous refilling time (VRT), venous clinical severity score (VCSS) for disease severity, and 6-min walk test (6-MWT) for functional capacity. Results The mean age of the patients was 49.48 & PLUSMN; 13.19 years, and the mean duration of disease was 9.18 & PLUSMN; 6.57 years. There was statistically significant positive association between MIP and VRT(r: 0.331, p: 0.009), 6-MWT (r: 0.616, p < 0.001) values, and there was negative association between MIP and VCSS(r: -0.439 p < 0.001) scores. Conclusion Evaluation of inspiratory muscle strength and elimination of its deficiency, providing interventions to approach normative values have the potential to contribute positively to the treatment of the patient.
Keywords: Diaphragm; maximum inspiratory pressure; photoplethysmography; disease severity; venous insufficiency